Implementasi Kebijakan Pembelajaran Tatap Muka Terbatas pada Masa Pandemi Covid - Dewi Purboningsih; Ardian Trio Wicaksono (Yayasan Letiges Konsultan Sosial, 2022)
This research was carried out with the aim of describing the implementation of the policy of implementing limited face-to-face learning during the pandemic and knowing the factors that influence the implementation of limited face-to-face meetings at SDIT Cendekia Banjarbaru. The research method uses a qualitative descriptive approach. Data collection techniques were obtained by using virtual interviews through google meet and document analysis. The data from this research were then analyzed through several qualitative descriptive techniques which included reduction, display and verification. The results showed that carrying out limited face-to-face learning at SDIT Cendekia Banjarbaru required some preparation in the form of socialization to the Parents and Teachers Gathering Forum, adjusting learning services, and paying attention to the completeness of the facilities and infrastructure needed during limited face-to-face meetings. In addition, there are factors that influence the readiness of the school to meet the needs of various facilities and infrastructure to support the implementation of limited face-to-face learing and the socialization of the school to parents of students through FSOG regarding the approval of the implementation of limited face-to-face learning.